PENGARUH PENGGUNAAN MODEL INKUIRI TERBIMBING DENGAN PENDEKATAN SAINTIFIK TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR PADA MATERI GETARAN GELOMBANG DAN BUNYI DI SMPN 08 KOTA BENGKULU - Diana Puspitasari; Eko Swistoro; Eko Risdianto (UNIB Press, 2017)
The main purpose of this research is to know the effect of using guided inquiry model with scientific approach to science process skill and learning outcomes. The main instrument used in this study is the test. The tests in this study include pretest and posttest. The sample was taken using purposive sampling technique class VIII 7 as experimental class and class VIII 9 as control class. The study was conducted from March 1 to March 31. Based on the results of data analysis found there is influence the use of guided inquiry model with scientific approach to science process skill. This can be seen on the score difference before treatment is given after treatment. The average score of each meeting pretest of 24.2 while the average posttest score of each meeting amounted to 62.9 so the difference in average score between posttest with prestest of 38.7. Based on the result of data using t-test two independent samples showed there is significant effect of using guided inquiry model with scientific approach to student learning outcomes. This is shown by thitung 2,444> ttabel 2,004. So it can be concluded that there is a significant influence the use of guided inquiry model with scientific approach to science process skills and student learning outcomes.